Diagnostic laparoscopy in the cat: 2. Common procedures. Issue 1 (January 2014) - Robertson, Elise; Webb, Craig; Twedt, David
Practical relevance: Minimally invasive techniques are becoming increasingly available in both first opinion and referral veterinary surgeries. Clients may be reluctant to pursue open surgery for the collection of biopsy samples in a sick cat but may be more open to a laparoscopic approach. Furthermore, a laparoscopic approach provides excellent visualization of the abdominal organs and enables high quality biopsies to be taken that are invariably more diagnostic than percutaneous needle biopsies. Although the feline patient is small in size, its distensible abdomen allows more room for surgical manipulation than afforded by a similar sized canine patient. Clinical challenges: Clinical challenges for the most part relate to mastering laparoscopic technique. Familiarity with the use of long instrumentation viewed on a two-dimensional screen is essential. Hemostasis is an important consideration and suitable instrumentation for achieving hemostasis should be available at all times. Insufflation of the abdomen carries its own challenges with regard to anesthesia and this is covered in an accompanying article in this Special Issue series. Aim: This article introduces the feline practitioner to basic techniques required to effectively utilize diagnostic laparoscopy within feline medical investigations. It focuses on the common procedures of liver biopsy, cholecystocentesis, pancreatic biopsy, kidney biopsy and laparoscopic-assisted intestinal biopsy. Evidence base: Information provided in this article is drawn from the published literature and the authors' own clinical experience.